2005
DOI: 10.1093/jn/135.10.2305
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Transport Is Decreased and Expression of the Lipid Transporters SR-BI, NPC1L1, and ABCA1 Is Downregulated in Caco-2 Cells Treated with Ezetimibe

Abstract: Data suggest that intestinal carotenoid absorption is a facilitated process. The present study was conducted to determine whether carotenoids and cholesterol share common pathways (transporters) for their intestinal absorption. Differentiated Caco-2 cells on membranes were incubated (16 h) with a carotenoid (1 micromol/L) with or without ezetimibe (EZ; Zetia, an inhibitor of cholesterol transport), and with or without antibodies against the receptors, cluster determinant 36 (CD36) and scavenger receptor class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
219
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(243 citation statements)
references
References 35 publications
9
219
2
1
Order By: Relevance
“…In CaCo-2 cells, differential and competitive uptake of α-carotene, β-carotene, lutein, and LYC has been reported [34]. Recently, scavenger receptor class B, type I (SR-BI) has been identified as a protein involved in intestinal transport of carotenoids in Caco-2 cells [35], and SR-BI is highly concentrated in human and rat liver and in steroidogenic tissues [36,37]. The specificity of transport and/or binding proteins is unclear, yet it is plausible that this specificity may depend on the number and/or location of conjugated double bonds present within carotenoids ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In CaCo-2 cells, differential and competitive uptake of α-carotene, β-carotene, lutein, and LYC has been reported [34]. Recently, scavenger receptor class B, type I (SR-BI) has been identified as a protein involved in intestinal transport of carotenoids in Caco-2 cells [35], and SR-BI is highly concentrated in human and rat liver and in steroidogenic tissues [36,37]. The specificity of transport and/or binding proteins is unclear, yet it is plausible that this specificity may depend on the number and/or location of conjugated double bonds present within carotenoids ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…At the intestinal level, b-carotene absorption is depending on three steps: (1) absorption at the enterocyte brush border membrane level, partly via the cholesterol transporters SR-BI and CD36 [11,71] but also by passive diffusion [83]; (2) enzymatic conversion of a fraction of absorbed b-carotene in a centric or eccentric fashion by the b-carotene 15,15 0 -monooxygenase BCMO1 (releasing retinal) or by the b-carotene 9 0 ,10 0 -dioxygenase, BCDO2 (releasing b-apo-10 0 -carotenal and b-ionone), respectively (Fig. 2, for review see [73].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%
“…[22][23][24] Besides, our results were consistent with data reported by other group, NPC1L1 transcription activity was inhibited while cells were treated with ezetimibe. 25 In addition, it has been reported that NPC1L1 promoter is regulated mainly by SREBP-2, a transcription factor-regulated cholesterol metabolism-related genes expression. 17 Both putative sterol regulatory elements and Ying Yang-1 (YY1)-binding sites are present in the promoter region of NPC1L1, suggesting that these transcription factors may regulate the NPC1L1 gene expression.…”
Section: Identification Of Npc1l1 Polymorphismsmentioning
confidence: 99%